2016
DOI: 10.1016/j.jad.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior in people with bipolar disorder: A systematic review and meta-analysis

Abstract: Adults with BD engage in high levels of sedentary behavior during waking hours. Given that sedentary behavior is an independent predictor of cardiovascular disease, future lifestyle interventions specifically targeting the prevention of sedentary behavior are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 40 publications
6
88
0
2
Order By: Relevance
“…People with SMI engage in significantly less vigorous exercise, and significantly greater amounts of sedentary behaviour than health controls (Stubbs et al 2016 a , b ; Vancampfort et al 2016 a ). This inactivity is predictive of a range of adverse health outcomes including obesity, diabetes and medical co-morbidity among people with SMI (Vancampfort et al 2013 a , b ; Suetani et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…People with SMI engage in significantly less vigorous exercise, and significantly greater amounts of sedentary behaviour than health controls (Stubbs et al 2016 a , b ; Vancampfort et al 2016 a ). This inactivity is predictive of a range of adverse health outcomes including obesity, diabetes and medical co-morbidity among people with SMI (Vancampfort et al 2013 a , b ; Suetani et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary lifestyle is a common problem among individuals with Bipolar Disorder [34] and may consequently affect youth offspring living with a Bipolar Disorder parent. The beneficial effects of exercise on depressive symptoms in broad samples of treatment seeking youth have been meta-analytically reviewed [35], but have not been specifically demonstrated in youth at risk for Bipolar Disorder.…”
Section: Resultsmentioning
confidence: 99%
“…rest during a walk, getting up for a drink during work), whereas self-report measures may not be sensitive to breaks. However, meta-analyses with adults with schizophrenia or bipolar disorder have found higher objective estimates of PA and SB 392,395,396 , which may be due to the different self-report measures used.…”
Section: Comparison Of Questionnaire and Accelerometer Datamentioning
confidence: 98%
“…Meta-analyses with adults with schizophrenia reported pooled accelerometer-derived time spent in SB, light activity and MVPA of 754 minutes/day (IQR=538-970) 395 , and 188 minutes/day (IQR=173-203) and 42 minutes/day (IQR=34-50), respectively 392 . Another meta-analysis with adults with bipolar disorder found that participants spent approximately 613 minutes/day (95%CI=390-837) in SB, and 210 minutes/day being physically active 396 . Differences between estimates of time spent in PA and SB could be because of the different sample characteristics: I recruited a sample across a range of mental illnesses, whereas previous research typically involves individuals with specific diagnoses 356,392,396 .…”
Section: Accelerometrymentioning
confidence: 99%
See 1 more Smart Citation